AB 21. Inhaler mishandling in chronic obstructive pulmonary disease - Antoniadou, Maria (Pioneer Bioscience Publishing Company, 2012)
BACKGROUND: To investigate the prevalence of inhaler mishandling in outpatients with chronic obstructive pulmonary disease (COPD) in a secondary hospital and their associated characteristics. PATIENTS AND METHODS: We enrolled 139 patients with confirmed diagnosis of COPD in stable condition. Gender, age, smoking status, degree of motivation to quit smoking, post-bronchodilator FEV(1), GOLD classification of airflow limitation, the MRC dyspnoea scale, co morbidities and treatment regimen for COPD was collected. Proper inhaler technique instructions were given to all patients. After 1 month period, patients demonstrated their inhaler technique and self-reported medication effectiveness and their perceived difficulty to use the inhaler were recorded. RESULTS: Patients (89% men) had a mean age of 69.4±9.6 years and an FEV(1) of 57.7±19% pred. Current smokers were 62 (44.6%). The majority [71 patients (51.1%)] were at stage ΙΙ. Of the participants, 65 (46.8%) made one or more mistakes during the demonstration. Gender, age, smoking status, dyspnoea, co morbidities and disease severity were not associated with inhaler misuse. We found no association between inhaler mishandling and the number of inhalers by patient. Inhaler mishandling was associated with self-reported ineffectiveness of medication (P<0.001), unwillingness to quit smoking (P<0.05) and perceived difficulty to use the inhaler (P<0.05). CONCLUSIONS: Inhaler mishandling is common in outpatients, even though they have been recently educated and it is not associated with gender, age, smoking status, airflow limitation and number of inhalers by patient. Less motivated patients to quit smoking and patients who consider the inhaler difficult to use are more prone to inhaler misuse.